Failing to Live the Sermon: The Influence of Spirituality and Nationality on Unethical Behavior Among Leaders of Christian Organizations - Biaggi, Carlos; Issa, John (European Journal of Applied Sciences, 2022)
Leaders of religious organizations are supposed to be role models of ethical behavior; however, sometimes they fail to live what they preach. Even though spirituality is a much-studied phenomenon in the business ethics literature, there is little research specifically exploring the influence of spirituality and nationality on unethical behavior among leaders of Christian organizations. Hence, adopting a post-positivist paradigm, this study will fill this void using a sample of 184 employees and students of a Christian University in the Philippines. This study found that the lower the spirituality of Christian leaders, the more favorable their attitude towards unethical behavior, and the higher their propensity to misbehave. However, it seems that they are not significantly affected by the level of transparency and/or corruption of their home countries. In addition, this study found that when controlling for the influence of spirituality students have a more favorable attitude towards misbehavior than employees. These findings offer great insights to academicians and practitioners in the business ethics, and in the Christian leadership disciplines.spirituality